Handicrafts and Traditional Arts: Driving Sustainable Growth in Village Tourism - Lubis, Tona Aurora; Firmansyah, Firmansyah; Masriani, Ida; Sari, Novita; Ningsih, Maryati (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
Traditional arts and crafts play a vital role in enhancing village tourism by attracting visitors, creating immersive cultural experiences, and contributing to economic sustainability. This study examines the impact of traditional performances and high-quality handcrafted products on tourist satisfaction and overall tourism success. Using a structured research approach, data were collected and analyzed to evaluate how arts and crafts influence tourism appeal, visitor engagement, and local economic benefits. The findings indicate that traditional arts significantly enhance visitor experiences through cultural performances, while traditional crafts reinforce destination identity by offering unique, high-quality souvenirs. Moreover, tourist satisfaction emerges as a key determinant of village tourism success, emphasizing the importance of well-managed arts and crafts initiatives. However, challenges such as financial limitations, lack of innovation, and inadequate marketing strategies hinder the full potential of these tourism assets. The study highlights the need for collaborative efforts among tourism managers, policymakers, artisans, and local communities to sustain and further develop traditional arts and crafts as integral components of village tourism. Strengthening policies, enhancing promotional strategies, and improving market accessibility are essential to ensuring long-term sustainability and economic growth in rural tourism destinations.